POTENCIALIDADES DE ÁGUAS SUBTERRÂNEAS NO MUNICÍPIO DE ANANINDEUA - Oliveira, Josafá Ribeiro de; Costa, Expedito Jorge de Souza; Centeno Júnior, Felisberto M.; Silva, Raimundo Nonato Maciel da (Águas Subterrâneas, 2001)
Resumo não disponivel.